Controlling Prescribing through “Preferred Drug” Targets—The Bavarian Experience - Gollnick, Julia; Zeschick, Nikoletta; Muth, Julia; Hörbrand, Franziska; Behnke, Kerstin; Killian, Peter; Sebastiao, Maria; Kühlein, Thomas; Donner-Banzhoff, Norbert (International Journal of Environmental Research and Public Health, 2024)
Background: The rising costs of drugs are putting health care systems under pressure. We report on the Bavarian Drug Agreement, which employs prescribing targets for preferred and generic drugs in ambulatory care. Under this agreement, providers are regularly profiled with individual feedback but also possible sanctions. We investigated the degree to which targets were being met (or not) and why failure occurred. Methods: We analysed prescribing data aggregated by practice for the quarter 1/2018. We chose eight specialisation groups and analysed their drug targets with a high prescribing volume, widely missed drug targets (<90%), and drugs preventing drug target achievement. Characterisation of drug targets and preventing drugs was undertaken. Results: Drug targets with a high prescribing volume are mostly achieved, while highly missed drug targets mostly do not affect the main indication area of the specialisation groups considered. Generic drug targets seem to be more easily achieved than recommended drug targets. Paediatrics accounts for the largest number of missed drug targets. Conclusions: The Bavarian tool implemented uses the prescribing volume (DDD) and price components to evaluate the prescription behaviour of physicians. Well-established drugs with demonstrated effectiveness, safety, and lower costs are preferred. Nevertheless, me-too drugs, combination drugs, costly innovations with unclear value, and drugs with application methods of variable convenience challenge the drug prescribers and are reasons for missed drug targets.
CRIS-Team Scopus Importer:2024-10-11
Keywords: ambulatory care/economics; budgets; cost control/trends; drug prescriptions; drug therapy/economics; drug therapy/trends